Foundations of Neuroeconomics as an Academic Field in Bulgaria - Ivantchev, Boyan (UNWE Yearbook, 2021)
The pioneering and innovative research in Bulgaria in the field of neuroeconomics uses fMRI (functional magnetic resonance imaging) and the BOLD method (Blood Oxygenation Level Dependent). We will explain the methods and scientific base of neuroeconomics with real experiments in that new scientific field. The experiments are made in a lab situated in university hospital UMBAL “St. Ivan Rilski” using GE Signa HDxt 1.5T scanner and specialized equipment of the Nordic Neuro Lab for audio-video psychological paradigms and brain stimulation. This unique and original research for the Bulgarian scientific community employs an interdisciplinary field of neuroeconomics to explain human behaviour and decision making and might be perceived as a foundation of the neuroeconomics as an academic field in Bulgaria.
Keywords: Neuroeconomics in bulgaria; fMRI experiments